Analysis of conductivity of ZnO/LDPE Composites. Issue 3 (July 2021) - Shen, Yubo; Zhang, Jian; Zhang, Dewen; Sun, Wei; Zhou, Hongyi; Liu, Heqian; Zhang, Peng
Abstract: The composites prepared by adding zinc oxide into polymer have been widely studied and applied because of their special properties of self homogenizing electric field distribution in non-uniform electric field, inhibiting space charge and electrical tree growth. In this paper, the effects of inorganic filler concentration and particle size on the conductivity of ZnO/LDPE Composites were studied by voltammetry combined with high voltage DC power supply and picoammeter to measure applied voltage and through current.